Karakteristik Organoleptik dan Profil Senyawa Volatil Rendang Bumbu Instan dengan Head Space Solid Phase Microextraction (HS-SPME) dan Gas Chromatography Mass Spectrometry (GC-MS) - Astutiningsih, Fitri; Nurlisa, Devi; Suhartatik, Nanik (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Rendang is a traditional dish with various spices, with meat and coconut milk as its primary ingredients. This research utilized instant rendang seasoning to prepare rendang in the form of bran, which was then tested for its organoleptic properties, chemical characteristics, and volatile compounds. The purpose of this study was to determine the chemical characteristics, organoleptic properties, and volatile compounds responsible for the strong aroma in the most preferred rendang seasoning, using Headspace Solid Phase Microextraction (HS-SPME) and Gas Chromatography-Mass Spectrometry (GC-MS) for sample extraction. A factorial completely randomized design was applied with two factors: brand of instant rendang seasoning (Indofood, Bamboe, and Kokita) and cooking duration (60 and 120 minutes). Data were analyzed using analysis of variance at a 95% significance level. The results showed that Bamboe brand instant rendang seasoning with a 120-minute cooking process was the most preferred by panelists. It exhibited a moisture content of 34.41%, ash content of 5.37%, protein content of 10.47%, fat content of 39.52%, and total sugar content of 10.54%. The hedonic test scores for color, aroma, texture, taste, and overall liking were 3.73, 2.93, 3.50, 3.57, and 4.00, respectively. Linalool, 1,2-Dihydropyridine, 1-(1-oxobutyl)-, and linalyl acetate were identified as the key compounds contributing to the strong aroma of the rendang seasoning.